The Minotaur and Picasso (Minerva, 2019)
This paper will start by establishing the comparison between the legend of the Minotaur as transmitted by Greek and Roman literature and art and Picasso’s version of this same legend. The study focuses on those works of Picasso with the Minotaur as a protagonist in the decade of the thirties in the last century. Beyond the formal and thematic influence, Picasso’s classicism is specially shown in the use of the myth. Artists and poets of Antiquity could use and manipulate myths to express interests and personal feelings. This use of the myth reaches its highest expression in numerous representations of the Minotaur which correspond to moral self-portraits of Picasso and which, through the years, constitute an intimate autobiography of the artist.
Keywords: Picasso; Minotaur; Classical Mythology; Classical Tradition